The translation of idioms and fixed expressions between Tshivenda and English - Nengovhela, Rofhiwa Emmanuel (My University, 2017)
This study examines the translation of idioms and fixed expressions between Tshivenḓa and English. The aim of the study is to explore factors that lead to the mistranslation of idioms and fixed expressions between the two languages. The study presents problems that are encountered in the translation of the idioms and fixed expressions between these languages and looks at translation strategies that can be used. In translating idioms, the translator encounters various difficulties that are not usually easy to overcome mainly due to lack of equivalence. It is rare to come across an idiom in the source language that shares the same form and meaning in the target language. In order to deal with the problems that arise in the process of translation, translators use various strategies. Among others, the translator must have extensive knowledge about the function of idioms in the source and target languages. From the data collected, the study revealed that there are numerous problems that the translator comes across in the process of translation. These include the ambiguity of idioms; idioms expressing meaning at a literal level; idioms that do not exist in the target language and the frequency of use of an idiom. The study adopted the qualitative research approach to collect and analyse data. Through use of this approach, it was noted that the translator needs to take into account cultures associated with the languages involved as well as the context in the translation process. The translation of idioms cannot be properly done without considering the impact of culture. A translator must be well-versed in the culture of both the source and target languages. It is important for one to know that language and culture are two entities that are inseparable. Idioms and fixed expressions express the uniqueness of the language and culture of the respective languages. Therefore, translators must have a comprehensive knowledge base of both languages and cultural context. From the recommendations made in this study, the following are the most prominent ones: Linguists should be exposed to idiomatic expressions in order to enhance their knowledge of the translation of idioms and fixed expressions. There are instances where idioms are translated literally because the translator does not understand or recognise the idiom. Therefore, this study recommends that translators need to learn more about idioms in order to have better understanding of translation of idioms and fixed expressions. Translators need to learn more about the translation strategies that are available to deal with the translation of idioms and fixed expressions. The first strategy is translation by using an idiom of similar meaning and form. This strategy involves using an idiom in the target language consisting of equivalent lexical items, which conveys roughly the same meaning as that of the source-language idiom. The second strategy is translation by idioms of similar meaning but dissimilar form. This strategy uses an idiom in the target language which has a meaning similar to that of the source idiom or expression, but consists of different lexical items. The third strategy is translation by paraphrasing. In this strategy, the translator transfers the meaning of an idiom using a single word or a group of words which roughly correspond to the meaning of the idiom but is not an idiom itself. The fourth strategy is translation by omission. This is used to completely omit the idiom from the target text where there is no close match between the items of the two languages. Where the idiom is very difficult for the translator, one tries to eliminate the whole part of the idiom. The fifth strategy is translation by a superordinate. This strategy is used to solve the problem of non-equivalence across languages because the hierarchical structure of semantic fields is not language specific. This strategy involves translation by a more neutral and less expressive word. Lastly, it is translation by cultural substitution which is a method that requires the replacement of a culture-specific item or expression with a target language one that has no exact meaning, but has an impact on the target reader. However, this study recommends translation by idioms of similar meaning with a dissimilar form. The researcher believes that this strategy provides the closest meaning of the idiom in the target language. Idioms might not be the same in form but the meaning can be derived from the idiom with a dissimilar form.
Thesis (Ph.D. (Translation Studies and Linguistics)) --University of Limpopo, 2017
Keywords: Translation; Idioms; Tshivenda; Idiomatic expressions; Tshivenda language, translation into English; Translation and interpreting -- South Africa; Tshivenda language -- idioms